Discursive knowledge and discursive thinking in the philosophical systems of Kant and Hegel G. - Ягодзінський, С.М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
The article analyzes the cognitive aspect of discursive thinking. Substantiates the thesis that discourse is the final part of the series of epistemological "dialogue, discussion, dialectic."